1858 Wis. Rev. Stat. 985, Of Proceedings to Prevent the Commission of Crime, ch. 175, § 18. - (:unkn) unknown (General Publisher, 1858)
If any person shall go armed with a dirk, dagger, sword, pistol or pistols, or other offensive and dangerous weapon, without reasonable cause to fear an assault or other injury or violence to his person, or to his family or property, he may, on complaint of any other person having reasonable cause to fear an injury or breach of the peace, be required to find sureties for keeping the peace, for a term not exceeding six months, with the right of appealing as before provided.
--
Keywords: CARRY